2020
DOI: 10.1002/er.5731
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant induced sonic fission: an effective strategy for biohydrogen recovery from sea grass Syringodiumisoetifolium

Abstract: Sea grass (Syringodiumisoetifolium) is a promising source of bioenergy such as hydrogen. Due to the complex cell structure, it requires a pretreatment process prior to fermentation. This study aims to increase the biohydrogen production from sea grass by enhancing the solubilization via surfactant induced sonic fission (SSF). Initially, sonic fission (SF) pretreatment alone was carried out intherange of power from 0.02 kW to 0.18 kW for 0 minutes to 60 minutes. At the optimum condition of SF (0.14 kW, 30 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The carbohydrate, protein, and lipid consumption rates were exacerbated in the T80/RGO-amended reactor up to 8.8 ± 3.7, 1.9 ± 0.6, and 0.72 ± 0.3 g/g VSS , respectively, corresponding to the degradation efficiencies of 82.7 ± 5.3, 78.3 ± 7.7, and 80.1 ± 8.7% (Figure a–c). Similarly, Rajesh Banu et al found that sonic fission and surfactant addition had a synergistic impact on the breakdown of organic fractions in seagrass . The carbohydrate and protein degradation efficiencies increased to 87.9 and 81.8% via surfactant-induced sonic fission, compared to 74.5 and 69.1% using sonic fission alone, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The carbohydrate, protein, and lipid consumption rates were exacerbated in the T80/RGO-amended reactor up to 8.8 ± 3.7, 1.9 ± 0.6, and 0.72 ± 0.3 g/g VSS , respectively, corresponding to the degradation efficiencies of 82.7 ± 5.3, 78.3 ± 7.7, and 80.1 ± 8.7% (Figure a–c). Similarly, Rajesh Banu et al found that sonic fission and surfactant addition had a synergistic impact on the breakdown of organic fractions in seagrass . The carbohydrate and protein degradation efficiencies increased to 87.9 and 81.8% via surfactant-induced sonic fission, compared to 74.5 and 69.1% using sonic fission alone, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Higher VFA production results in a lower pH value, which inhibits methanogenic activity and improves hydrogen productivity . Similarly, VFA production was increased to 1.3 g/L by the dual effect of sonic fission and surfactant addition compared to using sonic fission alone (0.86 g/L) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation